2020
DOI: 10.1111/joa.13261
|View full text |Cite
|
Sign up to set email alerts
|

Subject‐specific muscle properties from diffusion tensor imaging significantly improve the accuracy of musculoskeletal models

Abstract: Musculoskeletal modelling is an important platform on which to study the biomechanics of morphological structures in vertebrates and is widely used in clinical, zoological and palaeontological fields. The popularity of this approach stems from the potential to non-invasively quantify biologically important but difficult-to-measure functional parameters. However, while it is known that model predictions are highly sensitive to input values, it is standard practice to build models by combining musculoskeletal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 104 publications
(190 reference statements)
2
58
0
Order By: Relevance
“…Subject data were taken from Charles et al . [ 13 ], where 10 subjects were recruited (5 male and 5 female; age: 29 ± 3 years; body mass: 67.9 ± 9 kg; height- 175 ± 7 cm; BMI- 21.9 ± 1.6 kg m −2 ) and provided informed consent prior to participating in the study, in accordance with ethical approval from the University of Liverpool's Central University Research Ethics Committee for Physical Interventions (Reference no. : 3757).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subject data were taken from Charles et al . [ 13 ], where 10 subjects were recruited (5 male and 5 female; age: 29 ± 3 years; body mass: 67.9 ± 9 kg; height- 175 ± 7 cm; BMI- 21.9 ± 1.6 kg m −2 ) and provided informed consent prior to participating in the study, in accordance with ethical approval from the University of Liverpool's Central University Research Ethics Committee for Physical Interventions (Reference no. : 3757).…”
Section: Methodsmentioning
confidence: 99%
“…For each muscle of the lower limb, these median muscle fibre length values from DTI were used to estimate optimal fibre length (L f ) through the normalization to a generic optimal sarcomere length [2.7 µm] [25]. See Charles et al [13] for more details regarding this normalization. These values were then used to calculate PCSA using the following formula:…”
Section: (B) Muscle Architecture Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Continuing this work, Charles et al (2020) compared the accuracy of both subject-specific lower limb models and generic models built using data from both elderly and young individuals to muscle values obtained experimentally using an isokinetic dynamometer (Charles, Grant, Août, & Bates, 2020). Their results demonstrated that, while the generic models were not as accurate as the subject-specific models in predicting the experimental muscle values of particular individuals, generic models still have utility in musculoskeletal modelling studies.…”
mentioning
confidence: 99%